Role of flexible fiberoptic bronchoscopy in diagnosis of indefinate pulmonary infiltrates - Gupta, Raaghav; Purohit, Gopal; Choudhary, Balveer (International Journal of Research in Medical Sciences, 2019)
Background: Respiratory diseases commonly present and are mostly diagnosed by routine clinical assessment and noninvasive investigations. Bronchoscopy a novel diagnostic tool used in diagnosis of various infectious, inflammatory and neoplastic pulmonary diseases by retrieving samples from bronchial, alveolar and interstitial compartments of patients with lung infiltrates. We prospectively assessed diagnostic utility of bronchoscopy in patients who had respiratory symptoms, radiographic infiltrates and sputum smear is negative for acid-fast bacilli (AFB). Despite, recent technical innovations in bronchoscopy, routine FOB is practiced with high yield and cost effectiveness. Methods: A prospective study was performed in which bronchoscopy was performed in 40 patients between August 2018 and January 2019, who had respiratory symptoms, radiographic findings not consistent with any specific diagnostic entity and had sputum smear negative for AFB. Results: Out of total 40 patients, most 30 (75%) patients were from rural areas, more than half 24 (60%) of the patients were males. Out of total 21 (52%) of patients were current smokers. Most common presenting symptoms were cough 22 (55%) and hemoptysis 8 (20%) followed by fever 6 (15%) and weight loss 4 (10%). Tuberculosis was confirmed in 18 (45%) patients. Non tubercular diseases were diagnosed in 22 (55%). Interstitial lung disease (ILD) was diagnosed in 5 (12.5%), lung cancer in 5%, bronhiectasis in 7.5%, pneumonia in 12.5%, lung abscess in 2.5% and non-specific infection in 15%. Conclusions: Diagnostic utility of flexible bronchoscopy is ever growing and has certainly taken a turn from being a luxury to near necessity today. Its association with trivial complications makes it a safe procedure. Hence bronchoscopy should be considered in the evaluation of patients with respiratory symptoms, indefinate radiographic infiltrates and negative sputum AFB test.